Bay Days: The Managerial Revolutions and the Hudson’s Bay Company Department Stores, 1912‑1939 - Monod, David (Historical Papers / Communications historiques, 1986)
AbstractNorth American business history has long been dominated by a belief in the centrality of entrepreneurial innovation to corporate success. This paper looks at the history of the Hudson's Bay Company Stores Department and attempts to explain from within the traditional business-history framework the company's prolonged inability to create a profitable chain of department stores in Western Canada. During the interwar years the HBC was highly competitive in its marketing methods and up-to-date in its business structure. Indeed, the company's failure seems to have stemmed in large measure from these very factors, from its excessive reliance upon scientific management formulas and organizational theories. It was only during the Depression that the Bay was able to recoup its losses by moving away from the professional orthodoxies of the twenties, returning to older business structures, and deciding on a more consumer-oriented approach.